2021
DOI: 10.1002/jhbp.954
|View full text |Cite
|
Sign up to set email alerts
|

Mac‐2 binding protein glycosylation isomer predicts tolerability and clinical outcome of lenvatinib therapy for hepatocellular carcinoma

Abstract: Background Many patients with hepatocellular carcinoma present with impaired hepatic function, which often requires interruption or withdrawal of lenvatinib due to associated adverse events. We aimed to identify pre‐treatment predictors of tolerability and clinical outcome of lenvatinib therapy. Methods Eighty patients who received lenvatinib at our institution between 2018 and 2020 were included in this study. We assessed essential factors associated with prolonged progression‐free survival (PFS), using Cox p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In this context, data about a possible role for age are inconsistent: some studies showed no significant differences in AE occurrence between elder (age ≥75 years) and non‐elder patients, 40 whereas the study from Shimose et al shows advanced age as the most important variable for discontinuation of lenvatinib due to severe AEs 19 . A deeper understanding of molecular pathways may provide further clarification: for example, the baseline level of Mac‐2‐binding protein glycosylation isomer has been described as a predictor of both tolerability and clinical outcome of lenvatinib in HCC 47 . However, the possible role of potential confounding factors at baseline warrants further investigation 13 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this context, data about a possible role for age are inconsistent: some studies showed no significant differences in AE occurrence between elder (age ≥75 years) and non‐elder patients, 40 whereas the study from Shimose et al shows advanced age as the most important variable for discontinuation of lenvatinib due to severe AEs 19 . A deeper understanding of molecular pathways may provide further clarification: for example, the baseline level of Mac‐2‐binding protein glycosylation isomer has been described as a predictor of both tolerability and clinical outcome of lenvatinib in HCC 47 . However, the possible role of potential confounding factors at baseline warrants further investigation 13 …”
Section: Discussionmentioning
confidence: 98%
“…19 A deeper understanding of molecular pathways may provide further clarification: for example, the baseline level of Mac-2-binding protein glycosylation isomer has been described as a predictor of both tolerability and clinical outcome of lenvatinib in HCC. 47 However, the possible role of potential confounding factors at baseline warrants further investigation. 13 In conclusion, our study gives a comprehensive analysis of the association between AEs and efficacy of lenvatinib treatment in patients with HCC.…”
Section: Fatiguementioning
confidence: 99%
“…Mac-2 binding protein glycosylation isomer (M2BPGi) is a biomarker that was identified in patients with liver fibrosis 11 . In addition, studies have shown that M2BPGi is correlated with liver fibrosis stages 12 , is a predictor of lenvatinib tolerability and response in hepatocellular carcinoma 13 , regression of liver fibrosis after treatment in HCV 14 , is associated with advanced liver fibrosis in diabetes 15 , is correlated with liver stiffness 16 , and is a biomarker for survival after HCV eradication 17 , demonstrating the usefulness of this novel biomarker. M2BPGi is also a reimbursable clinical test in Japan but limited data is available in other Asia Pacific countries as highlighted in the 2016 Asian-Pacific Association for the Study of the Liver (APASL) consensus guidelines.…”
Section: Introductionmentioning
confidence: 99%